Scientific Communication between Spanish and English Educational Technology Journals. A Citation Analysis of eight Journals - Victoria I. Marín; Olaf Zawacki-Richter (Springer, 2019)
In order to disseminate the findings and recommendations from their studies, researchers publish papers in scientific journals in their subject area. Research communities thus emerge as a result of the communication between authors who cite other relevant papers. This study focuses on the relationships between Spanish and English research communities in the specific field of Educational Technology. We explore as hypotheses whether there are signs of scientific journal communication between authors in these two communities, and if the English authors reciprocate citations by Spanish authors. In order to verify them, a social network analysis was conducted by considering outgoing and incoming citations in eight open access journals (four in English and four in Spanish) published over ten years (2007-2016). The sample includes 3,407 articles, which were analysed using UCINET and Gephi software. The results show partial confirmation of the hypotheses, since two separate research communities were recognized, with almost no communication between them. However, the Spanish community was presented as more connected than the English one. We interpret these results by considering not only language factors, but also the journal roots and the particular subject field under consideration. Finally, we highlight some general recommendations to enhance future communication between these two education research communities.